The Role of Some Chemokines from the CXC Subfamily in a Mouse Model of Diabetic Neuropathy - Magdalena Zychowska; Ewelina Rojewska; Dominika Pilat; Joanna Mika (Journal of Diabetes Research)
The mechanism involved in the development of diabetic neuropathy is complex. Currently, it is thought that chemokines play an important role in this process. The aim of this study was to determine how the level of some chemokines from the CXC subfamily varies in diabetic neuropathy and how the chemokines affect nociceptive transmission. A single intraperitoneal (i.p.) injection of streptozotocin (STZ; 200 mg/kg) resulted in an increased plasma glucose. The development of allodynia and hyperalgesia was measured at day 7 after STZ administration. Using Antibody Array techniques, the increases in CXCL1 (KC), CXCL5 (LIX), CXCL9 (MIG), and CXCL12 (SDF-1) protein levels were detected in STZ-injected mice. No changes in CXCL11 (I-TAC) or CXCL13 (BLC) protein levels were observed. The single intrathecal (i.t.) administration of CXCL1, CXCL5, CXCL9, and CXCL12 (each in doses of 10, 100, and 500 ng/5 μL) shows their pronociceptive properties as measured 1, 4, and 24 hours after injection using the tail-flick, von Frey, and cold plate tests. These findings indicate that the chemokines CXCL1, CXCL5, CXCL9, and CXCL12 are important in nociceptive transmission and may play a role in the development of diabetic neuropathy.